World as (Arabic) Text: Mīr Dāmād and the Neopythagoreanization of Philosophy in Safavid Iran - Melvin-Koushki, Matthew (Studia Islamica, 2020)
The heavily Neoplatonic and antiquarian-perennialist tenor of Safavid philosophy is now widely recognized by specialists; but few have acknowledged its equally notable Neopythagorean turn. Likewise, that the primary mode of applied Neoplatonic-Neopythagorean philosophy as a Safavid imperial way of life was occult science has been ignored altogether, making impossible a history of its practice. The case of the Twelver Shiʿi sage-mage Mīr Dāmād - famed down to the present as an occult scientist - is here especially illustrative: for he was largely responsible for this Neopythagoreanization of Safavid philosophy, which saw the remarkable transmogrification of Ibn Sīnā himself into a Neopythagorean-occultist, by his espousal of a peculiarly Mamluk-Timurid-Aqquyunlu brand of philosophical lettrism (ʿilm al-ḥurūf) in at least three of his many works. The example of this imperial Neopythagoreanizing lettrist is thus crucial for understanding the intellectual and religiopolitical continuity of Safavid Shiʿi culture with Sunni precedent, as well as contemporary Persianate and Latinate parallels. Within Western history of science more broadly, Mīr Dāmād and the host of his fellow Muslim kabbalists must now be restored to the master mathesis narrative whereby scientific modernity is but the upshot of early modern Western philosophers’ penchant for reading the world as a mathematical text.